SISTEM LAYANAN ANTAR PADA RESTORAN BERBASIS ANDROID - Bagus Pratama, Endyatna Puthut; Sumarsono, Sumarsono; Tamatjita, Elizabeth Nurmiyati (Compiler, 2013)
The business restaurant is growing. In this fast business is need application mobile for customer satisfaction. This system his many applications. They are customer, manager, web kitchen and deliveryapplication. This application is using android Operating System. Using that application by maps for knowing the places o f customer. The results are 100% fo r delivery service, 93% to level o f effective and efficient, 97% to time service system and 97% o f delivery order system.